ON CONVECTION IN A VOLATILE-SATURATED MAGMA - Cardoso S.S.S.; Woods A.W. (My University, 1999)
When a saturated basaltic magma cools and crystallises in a shallow magma reservoir, gas bubbles may be exsolved from solution, thereby influencing the density, convective mixing and pressure evolution of the melt. In wet basaltic magmas, saturated with H2O, the production of small bubbles may dominate the density evolution of the mixture, causing a gradual decrease of the bulk density with cooling. Cool upper boundaries of the chamber may therefore become stable to convection while vigorous convection may develop as the bubbly-mixture rises from cold lower boundaries. The intensity of such bubble-driven convection may be an order of magnitude greater than purely thermal or compositional convection which arises in unsaturated melt. New laboratory experiments of such bubble-driven convection suggest that after a transient, an equilibrium bubble concentration is attained, and subsequently bubble-magma separation leads to build up of a layer of bubbles above the well-mixed bubble-laden melt . These results have some important implications for mixing when a volatile rich mafic magma is intruded below an evolved, less dense body of silicic magma. When the mafic magma becomes volatile saturated, then owing to cooling at its upper boundary, the bulk density in the upper boundary layer of the mafic magma will decrease owing to the exsolution of gas. If the density falls below that of the overlying silicic magma, then small plumes of buoyant bubble-rich mafic magma may rise from the boundary into the upper silicic layer. In addition, on saturation of the mafic magma, cooling at the lower boundary will begin to drive convection of bubble-rich melt. The mafic magma may eventually reach an equilibrium bubble concentration and, subsequently, the bubbles produced at the base of the layer will be supplied to the interface between the silicic and mafic layers. Large scale overturn of the mafic and silicic magmas can therefore only occur if, at the equilibrium bubble concentration, the bulk density of the bubbly mafic magma is smaller than that of the overlying magma; otherwise mixing continues through small plumes of vesicular mafic melt rising from the upper boundary layer. For basaltic magma in which CO2 is the dominant volatile phase, the generation of bubbles does not typically dominate the density evolution and the convective flows are similar to those in an unsaturated melt.
Keywords: VOLATILES; MAGMAS; DEGASSING; CONVECTION